Highly magnetizable superparamagnetic colloidal aggregates with narrowed size distribution from ferrofluid emulsion - Lobaz, Volodymyr; Klupp Taylor, Robin; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2012)
The formation of spherical superparamagnetic colloidal aggregates of magnetite nanoparticles by emulsification of a ferrofluid and subsequent solvent evaporation has been systematically studied. The colloidal aggregates occur as a dense sphere with magnetite nanoparticles randomly packed and preserved particle-particle separation due to chemisorbed oleic acid. The voids between nanoparticles are filled with solvent and free oleic acid. The latter was found to influence the formation of colloidal aggregates and their surface properties. The choice of surfactant, whether low molecular weight or polymeric, was shown to lead to the colloidal aggregates having tailored interfacial behavior. Magnetization measurements at ambient temperature revealed that the magnetite colloidal aggregates preserve the superparamagnetic properties of the starting nanoparticle units and show high saturation magnetization values up to 57. emu/g. The size distribution of magnetite nanoparticle colloidal aggregates produced by such an approach was found to be a function of emulsion droplet breakup - coalescence and stabilization kinetics and therefore is influenced by the emulsification process conditions and concentrations of the emulsion compounds. © 2012 Elsevier In
Keywords: Colloidal aggregate; Emulsion; Magnetite nanoparticle; Superparamagnetic particle